The importance of accounting disclosure in financial statements and its role in commercial banks A survey study in commercial banks based on survey lists - Ali Omer Mohammed; Rzgar Ali Ahmed (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
In recent years, interest has increased in the matter of disclosure. In fact, this interest in disclosure has not come from a free. Many external entities, shareholders and investors rely heavily on their decisions on information banks. These groups do not have the authority to obtain the information they need directly from the administration Banks. There is no doubt that the lack of disclosure requirements makes the data and information contained in the financial statements misleading, and this is reflected in the decision-making by the shareholder or investor interested in this information and data. It can be said that the bankruptcy of banks and the collapse of some financial markets is due primarily to lack of commitment to disclosure. Therefore, the commitment of banks to disclosure is one of the most important topics currently, and attention is due to the rapid spread of information technology and evidence As is well known, the accounting and auditing profession plays an important role in raising the efficiency of banks in general and commercial banks in particular and influencing investment decisions through the financial statements prepared and published by banks. These financial statements must provide the correct and sufficient information to investors in a timely manner to take their investment decisions on sound objective basis.